Immunomodulatory properties of cacao extracts – potential consequences for medical applications - Becker, Kathrin; Geisler, Simon; Ueberall, Florian; Fuchs, Dietmar; Gostner, Johanna (Frontiers in Pharmacology, 2013)
Anti-inflammatory properties of cacao, fruits of Theobroma cacao L. (Sterculiaceae), are well documented, and therapeutic applications are described for gastrointestinal, nervous and cardiovascular abnormalities. Most, if not all of these disease conditions involve inflammation or immune activation processes. The pro-inflammatory cytokine interferon-γ (IFN-γ) and related biochemical pathways like tryptophan breakdown by indoleamine 2,3-dioxygenase (IDO) and neopterin formation are deeply involved in their pathogenesis. Neopterin concentrations and the kynurenine to tryptophan ratio (Kyn/Trp, an estimate of IDO activity) are elevated in a significant proportion of patients with virus infections, cancer, autoimmune syndrome, neurodegeneration and coronary artery disease. Moreover, higher neopterin and Kyn/Trp concentrations are indicative for poor prognosis. When investigating the effect of aqueous or ethanolic extracts of cacao on IFN-γ, neopterin and Kyn/Trp concentrations in mitogen-stimulated human peripheral blood mononuclear cells, breakdown of tryptophan by IDO and formation of neopterin and IFN-γ were dose-dependently suppressed. The effects observed in the cell-based assays are associated with the antioxidant activity of the cacao extracts as determined by the cell-free oxygen radical absorption capacity (ORAC) assay. The influence of cacao extracts on IDO activity could be of particular relevance for some of the beneficial health effects ascribed to cacao: tryptophan breakdown by IDO is strongly involved in immunoregulation, and the diminished availability of tryptophan limits the biosynthesis of neurotransmitter serotonin. The inhibition of tryptophan breakdown by cacao constituents could thus be relevant not only for immune system restoration in patients, but also contribute to mood elevation and thereby improve quality of life. However, the available data thus far are merely in vitro only and future studies need to be investigated.